ASSESSING CONSUMER PROPENSITY FOR ENERGY-EFFICIENT PRODUCT ADOPTION - Nida Fatima; Hafiza Sobia Tufail; Majid Hussain; Fahad Javed Baig (International Journal of Contemporary Issues in Social Sciences, 2024)
This study educates about the behavioural intention of consumers in energy-efficient products. Consumer’s knowledge, confidence of consequences and environmental awareness was taken in account which establishes the belief, attitude and eagerness of environmental awareness respectively to predict the behavioural intention of consumers in energy-efficient products. For this purpose, quantitative research study was conducted and a questionnaire was developed for data collection. A survey was conducted through convincing sampling technique and 248 respondents from six different age groups were analyzed. Analysis of collected data was run through SPSS and PLS-SEM. The result shows that different factors impact the behavioural intention of consumers, that directly or indirectly influence purchase decision of energy efficient products. This study is practical for growing firms in energy efficient products sector. It is also represents clean environmental feature of using energy efficient products and positive affect of belief, attitude and environmental safety on behavioural intention Future concern for this study is to collect data in big cities if Pakistan.